Dual acute effects of tire microplastics and their leachates on Spirodela polyrhiza and phyllosphere bacteria - Osman, Donia M; Yuan, Wenke; Nyaga, Muthii Patrick; Monikh, Fazel Abdolahpur; Yang, Yuyi (Water research, 2025)
Tire microplastics (TMPs) significantly contribute to global plastic pollution, entering aquatic environments primarily through runoff, where they pose potential threats to aquatic ecosystems. Beyond the particles themselves, TMPs-derived leachates further exacerbate environmental risks. Despite growing concern over plastic pollution, the influences of TMPs and their leachates on aquatic systems remain largely understudied. To address this gap, we systematically evaluated how TMPs and their leachate (0∼1 % w/v) affect the growth, physiochemical responses, and phyllosphere bacterial community of model aquatic macrophyte duckweed (Spirodela polyrhiza), using natural particulate wood as a control. Our findings reveal that both unleached TMPs and leachates exerted detrimental effects on the growth of S. polyrhiza and inhibited the production of photosynthetic pigments. Unleached TMPs and leachate exposures triggered oxidative stress, as evidenced by alterations in antioxidant enzyme activities and lipid peroxidation levels. Notably, leached TMPs enhanced plant growth comparably to wood particulates, suggesting their potential to generate favorable conditions for aquatic plants at prevailing concentrations. Phyllosphere bacterial composition exhibited significant differences among treatments; TMPs exposures increased Aquabacterium abundance but induced a dose-dependent decrease in Pedobacter. Also, exposure to TMPs substantially altered the metabolic processes within phyllosphere bacterial communities, particularly affecting key microbial functions linked to nutrient metabolism, xenobiotic degradation, and stress adaptation. The correlations between plant properties and phyllosphere bacterial communities varied depending on the treatments, suggesting that the dual effects of TMPs may be attributed to the dissolved substances in the leachates. This study elucidates the complex interactions among TMPs, aquatic macrophytes, and phyllosphere microbiomes, highlighting the need for further investigation into the ecological consequences of TMP pollution in freshwater environments.
Keywords: Phyllosphere microbiomes; Aquatic macrophyte; Microplastic pollution; Phytotoxicology; Tire leachate